The Immunobiology of Cancer: An Update Review - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: The introduction of mechanism based targeted therapies to treat human cancers has been pledge as one of the results of three decades of remarkable progress of research into the mechanisms of cancer pathogenesis. We ponder how the description of hallmark principles is start to inform therapeutic development currently and may increasingly do so in the future.CONTENT: There are 10 biological capabilities involved as the hallmarks of cancer, during the multistep of human tumors development. These hallmarks simplify the complexities of neoplastic disease into a structured rational principles, includes sustaining proliferative signaling, eluding growth suppressors, resisting cell death, enabling replicative immortality, inducing angiogenesis, activating invasion and metastasis, genome instability, inflammation, reprogramming energy metabolism and evading immune destruction.SUMMARY: The 10 hallmarks of cancer, in other words, the tumor’s distinctive and complementary capabilities that enable its growth and metastatic dissemination, continue to provide a solid foundation for understanding the biology of cancer. The acknowledgment of the widespread applicability of these concepts will increasingly influence the development of new manners to treat human cancer.KEYWORDS: hallmark of cancer, cancer genome, inflammation, cancer immunology, metastasis